The Contrastive and Contextual Analysis of the Verb Run - Arina Isti'anah (Journal of Language and Literature, 2016)
Words become the source for understanding the meanings of language. In relation to the study of meanings, this paper attempts ate presenting the contrastive and contextual analysis of the verb RUN. The contrastive analysis is conducted in order to find the distinctive features of the word run and its synonymous words. After finding out the features differentiating the verb RUN, the contextual analysis is conducted. The contextual analysis displays the features which take place in the verb RUN in various fields. Based on the analysis, RUN has features of manner, agent, situation, distance or duration, direction and purpose. The feature AGENT dominates the feature of RUN in the contexts which equals 28%. The context of initiating the action causes the appearance of the feature AGENT. The feature distance or duration appears the least in the context of regular activity. The occurrence of the same feature in different contexts proves that a word shares the same feature in the different context, in other words, overlapping features happens.